Nuevas citas de monocotiledóneas adventicias para la Argentina - Hurrell, Julio Alberto (2009)
This paper includes five new records of adventitious monocots for Argentina: Aloe ciliaris Haw. (Asphodelaceae), Aspidistra elatior Blume (Convallariaceae), Sansevieria trifasciata Prain (Dracaenaceae), Phormium tenax J. R. Forst. & G. Forst. (Hemerocallidaceae) and Ornithogalum arabicum L. (Hyadnthaceae), belonging to order Asparagales. Also includes an evaluation of its status in the naturalization process: casual alien, naturalized.